2012
DOI: 10.1128/jcm.05817-11
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcomes of Complicated Skin and Soft Tissue Infections in Hospitalized Patients

Abstract: Complicated skin and soft tissue infections (cSSTIs) are among the most rapidly increasing reasons for hospitalization. To describe inpatients with regard to patient characteristics, cSSTI origin, appropriateness of initial antibiotics, and outcomes, we performed a retrospective cohort study in patients hospitalized for cSSTI. To identify independent predictors of outcomes, we performed multivariate analyses. Of 1,096 eligible patients, 48.7% had health care-associated (HCA) cSSTI and 51.3% had community-acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
75
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 25 publications
11
75
3
3
Order By: Relevance
“…The findings of this study correlate with the observations from many previous studies that SSTIs due to HA-MRSA are more prevalent among extremes of age, as in elderly and neonatal population. [6][7][8][9][10]14 On the other hand, we observed that the majority of CA-MRSA patients were children in the age group of 1-10 years (26.9%), with patients of age group greater than 50 contributing to only 5.7%. A study by Larsen et al showed similar results with children (1 to 10 years old) constituting 25.3% of all CA-MRSA cases.…”
Section: Discussionmentioning
confidence: 58%
“…The findings of this study correlate with the observations from many previous studies that SSTIs due to HA-MRSA are more prevalent among extremes of age, as in elderly and neonatal population. [6][7][8][9][10]14 On the other hand, we observed that the majority of CA-MRSA patients were children in the age group of 1-10 years (26.9%), with patients of age group greater than 50 contributing to only 5.7%. A study by Larsen et al showed similar results with children (1 to 10 years old) constituting 25.3% of all CA-MRSA cases.…”
Section: Discussionmentioning
confidence: 58%
“…Most of the HA-MRSA infections presented as cellulitis ,32(34.04%) followed by post operative wound infections, 27(28.72%), followed by abscess, 24(25.53%)). Zervos et al (2012) reported that health care associated completed SST were more likely to present as surgical site infections and ulcer. 12 Since children less than 10 yrs are not much involved among CA-MRSA patients, the risk factors for acquisition of CA-MRSA were not statistically significant in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Zervos et al (2012) reported that health care associated completed SST were more likely to present as surgical site infections and ulcer. 12 Since children less than 10 yrs are not much involved among CA-MRSA patients, the risk factors for acquisition of CA-MRSA were not statistically significant in the present study. HA-MRSA infections definitely possess many risk factors which poses a hazard to hospitalized patients.…”
Section: Methodsmentioning
confidence: 99%
“…In 2004, MRSA was the most commonly identifiable organism in patients with cSSSIs presenting at 11 emergency departments across the USA [2]. In a more recent retrospective study of cSSSIs in hospitalized patients, 66.4% of cultures grew S. aureus, of which 74.8% were MRSA [3].…”
mentioning
confidence: 98%